Non-Conventional Solutions to the Problem Treatment of Industrial Waste Water - I. N. Tursunova; X. Sh. Urunova; X. N. Esanbaeva (International Journal on Integrated Education, 2021)
This article discusses the problems of industrial wastewater treatment, and also provides the results of a theoretical study, thermodynamic substantiation and practical prospects for the use of nitrogen oxides (NO2, NO) instead of SO2 in the regeneration of cyanide solutions of the production of noble metals.